Outcomes of very high‐risk prostate cancer after radical prostatectomy: Validation study from 3 centers. Issue 3 (13th November 2018) - Sundi, Debasish; Tosoian, Jeffrey J.; Nyame, Yaw A.; Alam, Ridwan; Achim, Mary; Reichard, Chad A.; Li, Jianbo; Wilkins, Lamont; Schwen, Zeyad; Han, Misop; Davis, John W.; Klein, Eric A.; et al.
Abstract : Background: Among men with localized high‐risk prostate cancer (PCa), patients who meet very high‐risk (VHR) criteria have been shown to experience worse outcomes after radical prostatectomy (RP) in a previous study. Variations of VHR criteria have been suggested to be prognostic in other single‐center cohorts, but multicenter outcomes validating VHR criteria have not been described. This study was designed to validate VHR criteria for identifying which PCa patients are at greatest risk for cancer progression. Methods: Patients with high‐risk PCa undergoing RP (2005‐2015) at 3 tertiary centers were pooled. The outcomes of men with VHR PCa were compared with the outcomes of those who did not meet VHR criteria. The high‐risk criteria were a clinical stage of T3 to T4, a prostate‐specific antigen level > 20 ng/mL, or a biopsy Gleason grade sum of 8 to 10. The VHR criteria were multiple high‐risk features, >4 biopsy cores with a Gleason grade sum of 8 to 10, or primary Gleason grade pattern 5. Biochemical recurrence, metastasis (METS), and cancer‐specific mortality (CSM) were assessed with competing risks regressions. Overall mortality was assessed with Cox survival models. Results: Among 1981 patients with high‐risk PCa, men with VHR PCa (n = 602) had adverse pathologic outcomes: 37% versus 25% for positive margins and 37% versus 15% for positive lymph nodes ( P < .001 for both comparisons). Patients with VHR PCa also had higher adjusted hazard ratios for METS (2.78; 95% confidence interval [CI], 2.08‐3.72), CSM (6.77; 95% CI, 2.91‐15.7), and overall mortality (2.44; 95% CI, 1.56‐3.80; P < .001 for all comparisons). Conclusions: In a validation study of patients who underwent treatment for high‐risk PCa, VHR criteria were strongly associated with adverse pathologic and oncologic outcomes. Abstract : Very high‐risk prostate cancer is a new clinical risk stratum that is based on universally available staging data. Very high‐risk criteria are validated to predict metastasis and cancer‐specific mortality after curative local treatment.